Effect of modified calcium sulphate whiskers on free-radical/cationic hybrid photopolymers for 3D printing. (20th January 2020) - Jiao, Ting; Lin, Yucong; Liu, Yang; Liu, Jie; Lu, Gang
Abstract: This study presents and evaluates hybrid photopolymers applied to 3D printing. To obtain the hybrid system, epoxy acrylates (EA), epoxy resins and photoinitiators were compounded. As inorganic fillers are traditionally used to improve mechanical properties, calcium sulphate whiskers (CSW) coated with chitosan (CS) were modified by acryloyl chloride and the effects of the modification on hybrid photopolymers were investigated. The viscosity and volume shrinkage of the hybrid system were also evaluated. Fourier transform infrared measurements showed that hybrid photopolymers had a higher conversion. Meanwhile, the mechanical properties showed that the tensile strength of the cured samples containing 7% modified CSW was increased by 28% compared to that of pure resin. Additionally, the improvement of interface interaction between modified whiskers and hybrid photopolymers was observed by a scanning electron microscope. Dynamic mechanical analysis showed that the hybrid system, with the addition of 7% modified whiskers, exhibited a higher storage modulus and crosslinking density. This work, the first to use modified CSW on 3D printing to enhance the tensile strength of hybrid photopolymers, demonstrates that the photocured samples can contribute to high accuracy and resolution.